Machine learning bias in predicting high school grades - Costa-Mendes, Ricardo (2021)
Costa-Mendes, R., Cruz-Jesus, F., Oliveira, T., & Castelli, M. (2021). Machine learning bias in predicting high school grades: A knowledge perspective. Emerging Science Journal, 5(5), 576-597. https://doi.org/10.28991/esj-2021-01298